Phytochemical And Biological Activity Studies Of Garcinia Hombroniana - Jamila, Nargis (2014)
This study is the first report describing the phytochemical investigation and biological activities of the bark of G. hombroniana. The dichloromethane and ethyl acetate extracts of the bark of Garcinia hombroniana were separated by column chromatography to yield 4 new (DN8, DN9, EN2 and EN5) and 14 known (DN1-DN7, DN10, EN1, EN3, EN4, EN6-EN8) compounds. The structures of the new compounds were characterized by spectroscopic techniques such as UV, IR, and 1D and 2D NMR, together with EI and ESI-MS spectrometric methods. The known compounds were identified and confirmed by comparison of their spectroscopic data with the reported literature.